Retracted: Medication adherence and health belief model among hypertensive patients attending rural health centres of a tertiary care hospital in South India - A. U., Shameena; Badiger, Sanjeev; Kumar S., Nanjesh (International Journal Of Community Medicine And Public Health, 2017)
The article "Medication adherence and health belief model among hypertensive patients attending rural health centres of a tertiary care hospital in South India" is retracted by the Editor and Publisher, as per the request of corresponding author Dr. Shameena A.U. and co-authors, due to an unintended mistake. The Moriskys Medication Adherence Scale (MMAS-8) was used without proper permission.